2020
DOI: 10.3991/ijet.v15i07.13339
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Social Cohesion: The Development of E-Learning Management System Materials through Life Based Learning for Sociology of Religion Course

Abstract: The development of information and communication technology (ICT) encourages learning transformation to maximize it. Some transformations are through the development of E-Learning Management System (E-LMS). This paper explained the development of E-LMS material which is integrated with Life Based Learning in sociology of religion course. It integrated with life-based learning model through the ADDIE method which consists of Analysis, Design, Development, Implementation and Evaluation. The material was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It is proposed to use social learning analytics on the MOOC platform structured as network visualization in discussion forums [30]; in this case, each user is considered as a node, each response to a message is considered as a connection, and the tag cloud allows filtering connections and nodes based on the content. Tooltips help the user find a topic of interest and learn other user experience to draw conclusions about the interaction of students.…”
Section: Research Methodsologymentioning
confidence: 99%
“…It is proposed to use social learning analytics on the MOOC platform structured as network visualization in discussion forums [30]; in this case, each user is considered as a node, each response to a message is considered as a connection, and the tag cloud allows filtering connections and nodes based on the content. Tooltips help the user find a topic of interest and learn other user experience to draw conclusions about the interaction of students.…”
Section: Research Methodsologymentioning
confidence: 99%
“…Although this approach is widely used in vocational studies, it does not mean that the principles contained therein cannot be developed for education in general. Many researches have shown that life based learning can improve student's skill by designing curriculum [3], learning models [4] [5], and learning resources [6].…”
Section: Introductionmentioning
confidence: 99%
“…Through the development of mobile applications, the innovative creative work of learning can be encouraged. [11]- [14]. Innovative creative work in learning needs to be encouraged, through the development of mobile applications.…”
Section: Introductionmentioning
confidence: 99%